Country Partnership Framework for Benin for the Period of FY19-FY23 - World Bank Group (World Bank, Washington, DC, 2018)
This Country Partnership Framework (CPF) sets out the strategy for how the World Bank Group will support Benin in achieving higher rates of economic and social well-being over the period FY19-FY23. The Republic of Benin is a small country with a large potential for improving the well-being of its people. With a population of roughly 10.9 million people, Benin is renowned for the stability of its democratic system of government (since 1990). It is endowed with relatively fertile agricultural land, a long border shared with the region’s economic giant, Nigeria, and a strategic location as a hub connecting coastal and landlocked countries to the north. Despite these advantages, Benin’s development indicators are among the world’s lowest: the absolute number of people living in poverty has increased in recent years and conditions are particularly bad for women, people living in lagging regions in the north of the country, and young job-seekers. The country is also highly exposed to the environmental and social consequences of climate change, affecting agriculture productivity, health, food security, economic development, physical infrastructure, and water resources. The Government of Benin (GoB) proposes to improve its state of development through its Government Action Program 2016-2021 (Programme d’Actions du Gouvernement [PAG]). Adopted at the outset of the recently elected (2016) government of President Patrice Talon, the PAG starts with the premise that given Benin’s long history of democratic stability, its natural resource endowment, and its strategic location within West Africa, it can achieve much higher rates of economic and social well-being through a three-pronged approach: (a) consolidation of democracy, the rule of law, and good governance; (b) structural transformation of the economy; and (c) improvement of social wellbeing. The PAG is premised on the 2030 Agenda for Sustainable Development (embodying its related goals (SDGs) as well as the Paris climate agreement.